A strategic public communication campaign to raise awareness of ageing sucessfully among women in Singapore - Ang, Cecilia Shi Ting (2008)
Incandescence, authors of this FYP report, took the initiative to conduct a public awareness campaign to address the issue of ageing, in light of Singapore’s greying population and its pressing concerns. Recognizing the shortcomings of previous campaigns that lacked gender sensitive strategies, Incandescence collaborated with Women’s Initiative for ageiNG Successfully (WINGS) as an anchoring agency to promote the cause of ageing successfully among women for more targeted and effective outreach.